2014
DOI: 10.1128/ec.00148-14
|View full text |Cite
|
Sign up to set email alerts
|

Efg1 Directly RegulatesACE2Expression To Mediate Cross Talk between the cAMP/PKA and RAM Pathways during Candida albicans Morphogenesis

Abstract: The cyclic AMP/protein kinase A (cAMP/PKA) and regulation of Ace2 and morphogenesis (RAM) pathways are important regulators of the yeast-to-hypha transition in Candida albicans that interact genetically during this process. To further understand this interaction, we have characterized the expression of ACE2 during morphogenesis. In normoxic, planktonic conditions, ACE2 expression is very low in stationary-phase cells at both the mRNA and protein levels. Upon shifting to Spider medium, ACE2/Ace2p levels increas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
51
0
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 32 publications
(54 citation statements)
references
References 46 publications
2
51
0
1
Order By: Relevance
“…Ace2 was first identified in S. cerevisiae as target of the regulation of Ace2 and morphogenesis (RAM) pathway, which is conserved in fungi and ensures cell separation (Kurischko et al, 2005). Recently, cross-interaction of the RAM pathway with the PKA pathway was reported, in which Ace2 and the major hyphal regulator Efg1 determine morphogenesis of C. albicans in specific environments (Wang et al, 2009;Bharucha et al, 2011;Saputo et al, 2014;Desai et al, 2015). In this article we report that the transcription factor Ace2 functions downstream of the Cek1 MAP kinase pathway and is required to overcome impaired N-and O-glycosylation in C. albicans.…”
Section: Introductionmentioning
confidence: 99%
“…Ace2 was first identified in S. cerevisiae as target of the regulation of Ace2 and morphogenesis (RAM) pathway, which is conserved in fungi and ensures cell separation (Kurischko et al, 2005). Recently, cross-interaction of the RAM pathway with the PKA pathway was reported, in which Ace2 and the major hyphal regulator Efg1 determine morphogenesis of C. albicans in specific environments (Wang et al, 2009;Bharucha et al, 2011;Saputo et al, 2014;Desai et al, 2015). In this article we report that the transcription factor Ace2 functions downstream of the Cek1 MAP kinase pathway and is required to overcome impaired N-and O-glycosylation in C. albicans.…”
Section: Introductionmentioning
confidence: 99%
“…The Cbk1-Ace2 axis affects serum-induced filamentation One of our hypotheses at the outset of this screen was that a serum-based screen would identify unique CBK1 interactors because Ace2 was not required for filamentation (Kelly et al 2004) on serum but did affect Spider medium-induced filamentation (Saputo et al 2014). In our Spider medium screen, we identified a large number of Ace2 targets as CBK1 interactors.…”
Section: Resultsmentioning
confidence: 94%
“…In contrast, reduced gene dosage of the transcriptional regulator Ace2 affects that expression of the entire set of targets and, through this more global effect, leads to activation of compensatory pathways. Specifically, we have previously shown that the PKA pathway is hyperactivated in the absence of a fully functional Cbk1-Ace2 axis (Bharucha et al 2011) and contributes to the increased filamentation of ace2D/D under noninducing conditions (Saputo et al 2014). We further propose that one of the advantages of haploinsufficient phenotypes is that they may reveal subtle effects of pathways that otherwise may be overwhelmed by the compensatory response to complete loss of that pathway.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations